Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1093/ajh/hpv017
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholinesterase Inhibition Attenuates the Development of Hypertension and Inflammation in Spontaneously Hypertensive Rats

Abstract: Donepezil attenuated the development of hypertension in SHR probably involving antiinflammatory effects, indicating that acetylcholinesterase inhibition yields benefic effects for antihypertensive therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 35 publications
1
30
0
Order By: Relevance
“…Interestingly, there was no significant difference in HR among groups in the present study. Some studies have revealed a pyridostigmine‐induced increase in HR after the removal of adrenergic and cholinergic influences on the heart by propranolol and methylatropine in models of sympathetic hyperactivity‐induced cardiac dysfunction . These data indicate that pyridostigmine itself may increase HR, which may counteract the reduction of HR induced by ACh.…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, there was no significant difference in HR among groups in the present study. Some studies have revealed a pyridostigmine‐induced increase in HR after the removal of adrenergic and cholinergic influences on the heart by propranolol and methylatropine in models of sympathetic hyperactivity‐induced cardiac dysfunction . These data indicate that pyridostigmine itself may increase HR, which may counteract the reduction of HR induced by ACh.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, treatment with the peripherally-acting AChE inhibitor neostigmine fails to alleviate organ injury in murine endotoxemia [103] and pro-inflammatory cytokine responses associated with mechanical ventilation [104]. Very recently, treatment with the centrally-acting AChE inhibitor donepezil has been shown to increase vagal tone, suppress plasma TNF, IL-6 and IFN-γ levels, attenuate development of hypertension and prevent cardiac remodeling in spontaneously hypertensive rats [105]. In contrast, treatment with the peripherally-acting AChE inhibitor pyridostigmine fails to suppress plasma pro-inflammatory cytokine levels and reduce high blood pressure [105].…”
Section: The Remote Immunomodulatory Switches In the Brainmentioning
confidence: 99%
“…Very recently, treatment with the centrally-acting AChE inhibitor donepezil has been shown to increase vagal tone, suppress plasma TNF, IL-6 and IFN-γ levels, attenuate development of hypertension and prevent cardiac remodeling in spontaneously hypertensive rats [105]. In contrast, treatment with the peripherally-acting AChE inhibitor pyridostigmine fails to suppress plasma pro-inflammatory cytokine levels and reduce high blood pressure [105]. …”
Section: The Remote Immunomodulatory Switches In the Brainmentioning
confidence: 99%
“…The released NO can diffuse into the tunica media and activate the soluble guanylate cyclase (sGC) in vascular smooth muscle cells to cause vasodilation [23,24]. ACh is one of neurotransmitters in the autonomic nervous system, acting through the muscarinic receptors, that induces vasodilation through conduction of the translocation of eNOS, which then increases the level of NO [25][26][27][28]. Therefore, chronic administration of L-NAME leads to a decrease in the ability of ACh to produce NO, which then reduces vasorelaxation.…”
Section: Discussionmentioning
confidence: 99%